Hate Speech in Instagram Comments of DPR RI: A Forensic Linguistic Analysis - Putra, Valdi Giffari Rahmayati; Febriyatko, Angga; Busri, Hasan (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
This study aims to examine the comments on Instagram posts made by the Indonesian House of Representatives (DPR RI) through forensic linguistic analysis employing lexical semantics, speech act theory by Searle (1979), and the violation of politeness maxims according to Leech (2014). The research also focuses on identifying legal violations within these comments. The research methodology utilized is qualitative, employing a case study approach. Data collection was conducted through documentation by capturing all comments posted on the DPR RI's Instagram post on July 20, 2023, via screenshots. Data analysis was carried out qualitatively, primarily employing content analysis. Analytical steps included data organization, lexical-semantic analysis, identification and classification of speech acts and violations of politeness maxims, interpretation, and legal violation tracking. The research data comprised five hate comments on the DPR RI's Instagram post concerning the passing away news of its members on July 20, 2023. The analysis revealed that these comments contained negative and derogatory by using language that tarnished reputations and made unsubstantiated accusations. Some comments also violated politeness maxims, particularly the maxims of sympathy and praise. These actions potentially violate Article 310 (2) of the Indonesian Penal Code (KUHP) regarding defamation, Article 315 of the KUHP regarding minor insults, and Article 27 (3) of the Electronic Information and Transactions Law (UU ITE) regarding defamation through electronic media.